Unification Trails and Heritage Tourism Potential in Nepal - Bashyal, Keshav; Bhattarai, Ishwari (Unity Journal, 2021)
By the end of the eighteenth and early twentieth century, Shah Kings of Nepal succeeded in bringing together several small kingdoms under the Gorkha rule. King Prithvi Narayan Shah and his successors– led Gorkhali troops fought wars and travelled through several routes and trails across the Trans–Himalayas to expand the vast geography from Gorkha to Tista River in the east and Kangra fort in the west. In this background, this paper examines the importance of the unification trails, the routes used by Gorkhali troops, to unify neighboring principalities that eventually developed into modern Nepal. The unification trails are less explored issues in Nepal. In recent years, they have become popular historical sites for trekkers, visitors, researchers and historians to explore how Gorkhali soldiers skillfully expanded the territory. This is a descriptive and exploratory study based on historical facts and secondary resources. This paper concludes that the unification trails have historical and contemporary relevance for research as well as tourism potential. As one of the crucial forces to revitalize these trails, Nepali Army has constantly engaged with local people, and thus, promoting tourism activities. It offers the local communities the pathways of connection, avenues for development, basis for serving the daily livelihood and increase of income for the medium and small size entrepreneurs, workers, and other disadvantaged groups located along these trails.